The Limits of Medical Interventions for the Elimination of Preventable Blindness - Goldschmidt, Pablo (The Japanese Society of Tropical Medicine, 2014)
Background: Health authorities are working toward the global elimination of trachoma by the year 2020 with actions focused on the World Health Organization SAFE strategy (surgery of trichiasis, antibiotics, face washing and environmental changes) with emphasis on hygienist approaches for education. Objectives: The present survey was performed to assess the sustainability of the SAFE strategy 3 years after trachoma was eliminated from 6 villages. Methods: In February 2013 a rapid trachoma assessment was conducted in 6 villages of Kolofata’s district, Extreme north Region, Cameroon, where trachoma was eliminated in 2010. A total of 300 children (1–10 years) from 6 villages were examined by trained staff. Results: The prevalence of active trachoma (children aged > 1 and < 10 years) in 2013 was 15% and in at least 25% was observed absence of face washing and flies in their eyes and nose. Income level, quality of roads, hygiene, and illiteracy were similar in all the villages; they did not change between 2010 and 2013 and could not be analyzed as independent risk factors. Discussion: The heterogeneity of methods described for clinical trials makes it inappropriate to conduct meta-analysis for the present and for other SAFE-related trials. The results obtained after implementation the SAFE strategy (recurrence) reveal that the causes (infectious agents and dirtiness) and effects (illness) were not connected by illiterate people living under conditions of extreme poverty. So far, antibiotics, surgery and hygiene education are insufficient for the sustainability of trachoma elimination and highlight that hypothetic-deductive processes seem not operational after implementing the awareness campaigns. Trachoma recurrence detected in 2013 in sedentary populations of Kolofata receiving efficacious treatments against Chlamydia sp. suggest that the elimination goals will be delayed if strategies are limited to medical actions. Restricting efforts to repeated pharmacological and surgical interventions for people infected with susceptible bacteria could be understood as the hidden side of a passive attitude toward basic education actions.